2014
DOI: 10.3889/oamjms.2014.026
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Role of Aflatoxin B1 on the Liver of Wheat Milling Workers

Abstract: Aim: The study aimed to estimate oxidative role of aflatoxin B1 (AFB1) on the liver in wheat milling workers. Materials and Methods:Case-control study was conducted to compare between the levels of AFB1/albumin (AFB1/alb), liver enzymes (ALT, AST, GGT, and ALP), P53, MDA, GST, SOD, zinc and vitamin C in 35 wheat milling workers and 40 control subjects.Results: Statistical analysis revealed that ALT, AST, GGT, ALP, P53, MDA, GST and SOD in workers were significantly elevated compared to their controls. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…12 In a previous study, we found that the serum P53 was significantly higher in wheat mill workers with high serum levels of AFB1 compared to non-occupationally exposed controls. 13 The primary tumor biomarker for HCC is alphafetoprotein (AFP), a single polypeptide chain glycoprotein, and early diagnosis of HCC improves the survival of patients. Alpha-l-fucosidase (AFU) is a lysosomal enzyme found in mammalian cells and is a proposed tumor marker for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a previous study, we found that the serum P53 was significantly higher in wheat mill workers with high serum levels of AFB1 compared to non-occupationally exposed controls. 13 The primary tumor biomarker for HCC is alphafetoprotein (AFP), a single polypeptide chain glycoprotein, and early diagnosis of HCC improves the survival of patients. Alpha-l-fucosidase (AFU) is a lysosomal enzyme found in mammalian cells and is a proposed tumor marker for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…AFB1 has important public health implications where climatic conditions are favorable for the growth of AFB1-producing fungi. Aflatoxins are common food contaminants causing hepatotoxicity, immunosuppression, teratogenicity, mutagenicity, and carcinogenicity [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins influence oxidative status by increasing reactive oxygen species (ROS) levels and causing alteration in antioxidant enzymes [1,7,8]. Oxidative stress arises when ROS synthesis exceeds the ability of the antioxidant defenses to eliminate them, leading to oxidation of proteins, lipids, and DNA [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations